Menopause, A symptom of change! (Proceedings of the World Conference on Women’s Studies, 2019)
125,873,412 number of women are going through menopause in India. However, the impact of patriarchal structure reigns over every aspect of a women’s existence in Asia. From health and education to simple neglect in all aspects social or religious. From shaming the menstrual cycle to ignoring her menopausal cries for help, women are subjected to many pervasive discriminations. Gender bias exists in all rural and urban societies as a women’s wellbeing takes a backseat as she is not considered the prime provider for the family unit. Many women are not even aware of the symptoms of menopause. Symptoms are treated as a disease! A methodical approach whereby women across the spectrum of society were interviewed along with with their family members to get first-hand insight on women health-related issue in urban India. Secondary data was gathered through interviews conducted with medical practitioners and other free resources available on the world wide web. An urban-based campaign is designed within the academic parameters of Communication Design at ISDI, which seeks to educate society and women at large about the changes that can occur both on the conscious and subconscious level and how to deal with them. A holistic approach whereby educating society at large on a topic not discussed openly as society is handicapped by the male customized versions of “it being a women’s problem only”! Targeting this issue will benefit women in India and change mindsets of a regressive society which needs to address women related issues by adopting a healthy attitude.
Keywords: Menopause; Urban India; Women; Women's right; Patriarchy; social communication